Fluorescent gold nanoparticles with chain-end grafted RAFT copolymers: influence of the polymer molecular weight and type of chromophore. Issue 44 (24th October 2016) - Cepraga, Cristina; Favier, Arnaud; Lerouge, Frédéric; Alcouffe, Pierre; Chamignon, Cécile; Lanoë, Pierre-Henri; Monnereau, Cyrille; Marotte, Sophie; Ben Daoud, Edna; Marvel, Jacqueline; Leverrier, Yann; Andraud, Chantal; et al.
Abstract : Fluorescence of gold nanoparticles functionalized with chain-end grafted RAFT copolymers increases with polymer corona thickness. Abstract : Fluorescent gold nanoparticles (GNPs) were prepared by chain-end grafting of RAFT copolymers bearing multiple fluorophores distributed along the chain. Two different synthetic approaches in water were first studied with well-defined and biocompatible homopolymers. Both led to very stable samples and the corona thickness at the gold surface increased with the polymer molecular weight. The two-step ligand exchange approach was then selected to synthesize GNPs grafted with polymer–chromophore conjugates exhibiting different molecular weights, backbone architectures and chromophores. Again, the thickness of the organic corona increased with the polymer molecular weight but was also dependent on the conformation of the conjugate chains which depends on the nature of the chromophores. By adjusting these parameters, it was possible to control the average chromophore–gold distance which is of paramount importance for the fluorescence properties of the nanoparticles. We indeed showed that the fluorescence of the hybrid nano-objects increased with the corona thickness.